Single or multiple encounters of general anaesthesia do not cause any cognitive dysfunction: Findings from a retrospective population-based, case-control study - Huang, Zeqing; Wang, Nan; Suo, Liangyuan; Wang, Mingyu (Pakistan journal of pharmaceutical sciences, 2018)
General anesthesia and surgery have been associated with acute cognitive impairment in several elderly individuals. Present study was conducted to determine whether the general anaesthesia exposure and cognitive dysfunction are linked or not. This is a China-based retrospective, population-based and case-control study. Using Chinese database inhabitants of Shenyang, China, incident cases detected with cognitive abnormalities between January 2007 and December 2012 were identified. With respective to every incident case, age- and gender-matched control subject was chosen among the general population pool of Shenyang inhabitants who were not having cognitive anomalies in the year. Medical records were scrutinized to examine the exposures to surgical procedures necessitating anesthesia after 45-years of age. We examined 577 cases of cognition-impaired (dementia) patients, every incident case with a conforming control subject. Among the cognitive impaired patients, 414 (71.7%) underwent 821 surgical operations needing general anesthesia exposure; of the controls, 404 (70%) underwent 833 surgical procedures. The present study found that general anaesthetic agents encounter was not markedly associated with cognitive anomalies (odds ratio, 0.87; 95% CI, 0.71-1.09; P=0.29). Moreover, no substantial relation was observed when the anaesthetic agents encounter was measured as number of surgical operations (odds ratios (OR), 0.83, 0.89, and 1.0 for 1, 2-3, and 4 exposures, correspondingly, matched with none; P=0.52). Our present work witnessed no substantial link between surgical procedures requiring single or multiple general anesthesia exposure post 45-years of age and cognitive dysfunction.